2022
DOI: 10.1002/qua.26982
|View full text |Cite
|
Sign up to set email alerts
|

A prospectus for thickness dependent electronic properties of two‐dimensional metals using density functional theory calculation

Abstract: The properties of elemental metals have long been known, but the effect of two dimensionality on their electronic properties remain unclear. Scrutiny of the facet and thickness dependent electronic properties of ultrathin two‐dimensional (2D) metal layers is therefore of profound interest. Herein, an attention has been devoted to investigate the electronic properties of one to four atom thick layers of 45 elemental metal along (100), (110), (001)/(111) facets using density functional theory calculations. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…39,40 2D metal flatlands have received widespread research attention from the scientific community in the past few years. [41][42][43][44][45][46][47][48][49][50][51][52][53][54] Significant efforts have been made to probe the structure and stability of ultrathin 2D metal layers. 43,[55][56][57][58][59][60][61] A recent study by Koskinen and co-workers revealed that the metals can be stabilized as 2D patches inside the pores of graphene and Cu forms the best stable patch among the 45 elements studied.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 2D metal flatlands have received widespread research attention from the scientific community in the past few years. [41][42][43][44][45][46][47][48][49][50][51][52][53][54] Significant efforts have been made to probe the structure and stability of ultrathin 2D metal layers. 43,[55][56][57][58][59][60][61] A recent study by Koskinen and co-workers revealed that the metals can be stabilized as 2D patches inside the pores of graphene and Cu forms the best stable patch among the 45 elements studied.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] For instance, reducing the thickness of the metallic slab to a monoatomically thin membrane substantially improves their work function, and electronic and magnetic properties due to a reduction in their out-of-plane coordination. [27][28][29] Furthermore, in the context of catalysis, only the exposed surface in the bulk metal can be utilized for catalysing a chemical reaction, whereas singleatom catalysts (SACs) can achieve 100% atom utilization. 30,31 However, the use of SACs limits the co-adsorption of multiple reactants that may be involved in complicated reactions due to the unavailability of sufficient active space.…”
Section: Introductionmentioning
confidence: 99%
“…Much research is currently being undertaken into the stability, properties, and applications of metallic layers, particularly since the potential of graphene was first identified. [27][28][29][42][43][44][45][46][47][48] Despite many advances, the field of ultrathin metals is still in its infancy and there remains plenty of opportunity for new discoveries because the periodic table is mostly full of metallic elements. 16,49 Even though theoretical simulations have predicted the stability of the freestanding monoatomically thin membranes of metals, the experimental realization of these extended layers is often challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation